Electrochemical and Spectroscopic Studies on the Interaction between 1-(2-Pyridylazo)-2- naphthol and DNA - Niu, Shu-Yan; Zhang, Shu-Sheng; Xu, Hua; Jiao, Kui (Asian Journal of Chemistry, 2010)
Cyclic voltammetry was used to study the interaction between salmon sperm DNA and 1-(2-pyridylazo)-2-naphthol (PAN) which was dissolved in the mixture of ethanol and water. PAN had irreversible oxidation peaks in 0.2 mol Lnothing sup -1 Britton-Robinson (B-R) buffer solution at pH 4.80 on a glassy carbon electrode (GCE). After adding certain concentration of dsDNA, the oxidation peak current of PAN decreased. It was further investigated by UV-Vis spectroscopy and fluorescence spectroscopy. The hypochromic effect of the absorption peak and phenomena of bathochromic effect appeared. In addition, the increases of fluorescence were observed after dsDNA was added to the solution of PAN. Quenching fluorescence phenomenon was observed in EB-DNA system when PAN was added. All the experimental results showed that the binding mode of PAN with dsDNA was intercalative binding. The binding ratio of the DNA-PAN association complex was calculated to be 1 : 2 and the binding constant was 4.56 x 105 L2 mol-2.